2018
DOI: 10.1051/e3sconf/20184900062
|View full text |Cite
|
Sign up to set email alerts
|

Analytical meanders of selected systems for thermo-renovation of historical buildings

Abstract: The article contains an analysis of selected systems for thermorenovation of vertical partitions in protected buildings. Historical buildings often require thermo-renovation, but in practice their "insulation" can be applied only internally on partitions without decorations. Internal thermorenovation methods can be classified according to heat exchange and moisture transport. For the purpose of this paper, the methods were analysed in terms of diffusion-open and diffusion-closed systems, and compared in a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They also indicated that it is not necessary to conduct extremely dense scans, which consequently translates into saving time otherwise required for making measurements. The moisture analysis of historic buildings should be carried out thoroughly, the best results are obtained by conducting in situ examinations [49]. Mycological tests reveal the presence of various species of fungi, in particular toxicogenic and wood-degradable species.…”
Section: Discussionmentioning
confidence: 99%
“…They also indicated that it is not necessary to conduct extremely dense scans, which consequently translates into saving time otherwise required for making measurements. The moisture analysis of historic buildings should be carried out thoroughly, the best results are obtained by conducting in situ examinations [49]. Mycological tests reveal the presence of various species of fungi, in particular toxicogenic and wood-degradable species.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of revitalisation of historic tenement houses, the scope of activities largely depends on the state of preservation of the historic place [10]. All actions should be preceded by a diagnosis of the technical condition of buildings, taking into account historical changes in building development [5][6][7][8][9][11][12][13][14]. Diagnostics of individual buildings will allow determining the scale of needs in the revitalisation programme [1][2][3][5][6][7].…”
Section: Introductionmentioning
confidence: 99%